2007
DOI: 10.1007/s10641-007-9308-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and microchemistry of abnormal otoliths in the ayu, Plecoglossus altivelis

Abstract: The sagittal otolith morphology and microchemistry of reared juvenile ayu, Plecoglossus altivelis, were examined to describe the occurrence and microchemical characteristics of the abnormal otoliths in this species. Juvenile ayu (N=31) were collected in June 2004 at three different locations, Wakayama, Kumamoto, and Biwa Lake in Japan, where they were being reared in freshwater aquaculture ponds after having been collected in the wild as larvae. Otolith abnormality was found in the sagittae of 26% (N=8) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…A vateritic asteriscus is frequent in several teleosts (Lowenstam & Weiner, 1989;Campana, 1999;Falini et al 2005;Lenaz et al 2006), whereas a vateritic sagitta is characteristic of ancient species such as Ciclostomata, Polypterus and sturgeons (Carlstrom, 1963). It is, however, occasionally present as an abnormality (Gauldie, 1986;Ma et al 2007) or in juvenile (Tomàs et al 2004;Sweeting et al 2004) samples. Its constitutive presence in adults of a modern Notothenioid cannot be related to external factors such as stress or infections (Iguchi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vateritic asteriscus is frequent in several teleosts (Lowenstam & Weiner, 1989;Campana, 1999;Falini et al 2005;Lenaz et al 2006), whereas a vateritic sagitta is characteristic of ancient species such as Ciclostomata, Polypterus and sturgeons (Carlstrom, 1963). It is, however, occasionally present as an abnormality (Gauldie, 1986;Ma et al 2007) or in juvenile (Tomàs et al 2004;Sweeting et al 2004) samples. Its constitutive presence in adults of a modern Notothenioid cannot be related to external factors such as stress or infections (Iguchi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Its constitutive presence in adults of a modern Notothenioid cannot be related to external factors such as stress or infections (Iguchi et al, 2003). Rather, local changes in Sr, Na and K concentrations (Gauldie, 1986(Gauldie, , 1996Tomàs & Geffen 2003;Ma et al 2007) or the occurrence of a genetic mutation provide a better explanation. In the Chinook salmon, for example, it has been demonstrated that vaterite replacement is under single-locus genetic control and that this may be overridden by temperatures above or below an optimum range (Gauldie, 1986;Gauldie & Nelson, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…; Tomas & Geffen ; Ma et al . ). The shift from aragonite to vaterite formation is linked to changes in the protein matrix.…”
Section: Consequences Of External Factorsmentioning
confidence: 97%
“…Vaterite otoliths have also been observed occasionally in individuals instead of aragonite, and this substitution of morph may be linked to fish condition and especially welfare in the aquaculture environment (David et al 1994;Tomas & Geffen 2003;Sweeting et al 2004;Oxman et al 2007). Vaterite otoliths are more prevalent in aquaculture fish, occurring with a frequency of 50-80% of hatchery fish in some cases, compared with 3-20% in samples of wild fish (David et al 1994;Bowen et al 1999;Tomas & Geffen 2003;Ma et al 2008). The shift from aragonite to vaterite formation is linked to changes in the protein matrix.…”
Section: Environmental Information Content Of the Otolithsmentioning
confidence: 99%
“…The structure of vaterite differs markedly from aragonite, with the former typified by decreased density (Tomás & Geffen, 2003), increased translucency (Tomás et al , 2004; Ma et al , 2008) and less defined growth increments (Melancon et al , 2005; Tzeng et al , 2007). Biomineralization of these polymorphs may be physiologically (Gauldie, 1993; Bowen et al , 1999) or genetically (Gauldie, 1993; Brown & Severin, 1999; Söllner et al , 2003) controlled and related to spatially non‐uniform protein and chemical gradients in the surrounding endolymph (Payan et al , 1999).…”
Section: Introductionmentioning
confidence: 99%